Study of the Implementation of Knowledge Management: A Case Study of PT GMF AeroAsia - Muhdiantini, Cindy; Yani, Mega Fitri; Harizillah, M. Ahyar; Rahman, Ilham Auliya (STKIP PGRI Tulungagung, 2025)
PT Garuda Maintenance Facility AeroAsia Tbk (GMF AeroAsia), as one of the leading aircraft maintenance service providers in Indonesia, recognizes the importance of Knowledge Management in supporting its business growth. Since its establishment in 2002, PT GMF AeroAsia has transformed from a subsidiary of Garuda Indonesia into an independent business entity serving various domestic and international airlines. This study aims to examine the implementation of Knowledge Management at PT GMF AeroAsia. The study employs a comprehensive literature review method utilizing various sources such as Google Scholar, Scopus, and company reports. The research findings indicate that PT GMF AeroAsia has successfully integrated Knowledge Management into various aspects of the company. Knowledge Management has become the foundation for PT GMF AeroAsia to continuously enhance competence and innovation in the competitive Maintenance, Repair, and Operation (MRO) industry. This study provides a deeper understanding of the implementation of Knowledge Management at PT GMF AeroAsia and contributes to the development of Knowledge Management in the aviation industry.